Music and its teaching: invisible pedagogies, other windows to the world - Anderson Brasil; Celso Luiz Prudente (Universidade Federal do Norte do Tocantins, 2021)
This essay aims to bring to light other ways of learning and teaching music, with the object of revisiting musical practices existing in different parts of Brazil, which are invisible in disparate music courses. In this reflective weaving, experiences and conceptual immersions acquired in diverse sociocultural contexts will be interposed. Through dialogues with fundamental theorists such as Brandão (1983) and Prudente (2019), the deconstruction of the hegemony of Western music in relation to the ancestral knowledge of traditional peoples will be the guardians and maintainers of emancipatory musical practices, which intersect in different dimensions of making and teaching music.